Desenvolvimento de um modelo computacional do balanço social sistêmico dinâmico - Rodrigues, Marília (Universidade do Vale do Rio dos Sinos, 2014)
The difficulty to visualize the return that the investment in the social area can generate for society and the country economy, consequently makes both companies and the government, do not have the actual magnitude of the consequences of these investments over time. Within this context, the present research aimed to develop a computational model of a Systemic Dynamic Social Balance to view the multiplier effect generated by the investments of the Brazilian government in the social area. The research method adopted was the Design Science Research that is characterized by the construction and evaluation of artifacts developed for the purpose of to solve a problem. In the first phase of the research, was defined the problems involved in this study and drafted up the theoretical framework where the main themes for the development of the research were discussed. In the second, was selected the variables that were used to construct a systemic framework. At this stage was also developed a computational model pilot and computational model of a Systemic Dynamic Social Balance. In the third and final phase was created and simulated up some scenarios. The results generated by the scenarios were used to calculate the multiplier effect, which considers the evolution of GDP and costs on health and education. Whereof the calculation of the multiplier effect it was concluded that governmental social investments generate positive impacts on the economy of the country. Investment in education showed the greatest impact on GDP. However, one must make a combination between investments in health, education and infrastructure in view of the interdependence between investments.
Keywords: Balanço social; Balanço social sistêmico; Dinâmica de sistemas; Balanço social sistêmico dinâmico; Efeito multiplicador; Social balance; Systemic social balance; System dynamics; Systemic dynamic social balance; Multiplier effect; ACCNPQ::Engenharias::Engenharia de Produção